Survival and behavior of juvenile salmonids (Oncorhynchus spp.) in a large water diversion revealed with acoustic telemetry - Steven C. Zeug; Myfanwy E. Johnston; Matthew B. Espe; Andrew J. Kalmbach; Eric D. Chapman; Michele N. Johnson; Javier B. Miranda (Animal Biotelemetry)
Abstract Diversion of freshwater is a common practice worldwide that is often associated with negative impacts on native fish. Assessment of the survival and behavior of fish around water diversion infrastructure is critical to formulate strategies to mitigate potentially negative effects. In the Sacramento–San Joaquin Delta (USA) a large diversion operated by the state of California has been documented to impose mortality on threatened juvenile salmonids that are entrained there. The diversion includes a salvage system that separates fish from water downstream of a forebay. However, there is mortality associated with the entrainment and salvage process. Survival estimates based on previous batch-tagging studies are applied within regulatory frameworks to manage salmonid mortality associated with the diversion. An independent science review found that variation in survival and movement behavior through the facilities was the largest source of uncertainty in models estimating the magnitude of mortality. We performed a 6-year acoustic telemetry study to define survival in specific components of the facility, characterize variation in survival over time, and relate survival probabilities to the characteristics of individual fish. We found that survival is highly variable among specific locations of the diversion and within and between years. In addition, the size and run/species of juvenile salmonids were best supported as covariates to explain patterns of survival. The data presented here represent the most comprehensive study of salmonid survival through this large diversion and can be used to improve models of diversion-related mortality and provide a baseline against which mitigation measures may be evaluated.